Tensiones entre la educación tradicional y el uso de TDIC en la enseñanza remota de emergencia durante la pandemia - Galizia, Fernando Stanzione; Biazolli, Caroline Carnielli; Vilela, Denise Silva; Carnio, Michel Pisa; Bretones, Paulo Sergio (Universidad de Costa Rica, 2022)
This article aims to discuss how was organized, during the period of social isolation due to the pandemic of COVID-19, in 2020, the teaching work of teachers of Basic Education, from different areas of the education networks of São Carlos, an inland city of São Paulo – Brazil. Through the application of an online questionnaire, between the months of May and June 2020, we seek to describe, analyze and interpret which were the influences of emergency remote teaching and the use of Digital Information and Communication Technologies (DICT) in the personal and, above all, professional behavior of these teachers. The results, presented in a dialogue with the ideas of a varied set of authors, indicate that, in general, in the pandemic context, traditional aspects of school education remained recurrent, in a direction contrary to the demands of computerization imposed by the pandemic. The conclusions of this text lead us to ponder on the relevance of teachers and students to have a real understanding of new technologies, in order to use them reflexively and pedagogically; about the need for all these agents to be immersed in digital culture; and on the urgency of rethinking some issues in the face of what we have been experiencing, such as what are the purposes of education, the social and political role of the teacher, the notion of teaching autonomy; among others.